Academic Administration Strategies Toward Exellence of Pravate School in the Northeastern Region - Yasothon, Wirawit; Bangwiset , Suchat; Nuntee, Sakdinaporn (Dhammathas Academic Journal, 2025)
The purposes of this research were 1) to explore the components of academic management that lead to excellence, 2) to assess the current and desired conditions as well as the needs for academic management, 3) to develop strategies for achieving academic excellence, and 4) to evaluate these strategies in private schools in the Northeastern region of Thailand. The research methodology is divided into 4 stages: Phase 1: Document analysis of six private schools to identify components of academic administration for excellence Phase 2: Study of current and desired conditions and needs, involving 435 participants (school administrators and academic teachers) selected using Krejcie and Morgan’s table and two-stage sampling. Phase 3: Development of academic administration strategies through two steps: Step 1: Multi-case study of three schools using semi-structured questionnaires. Step 2: Group discussion with nine experts using discussion records. Phase 4: Experimentation and evaluation of the strategies in two schools, with data from nine academic teachers. Quantitative data were analyzed using frequency, percentage, mean, standard deviation, and need importance index, while qualitative data were analyzed through content analysis. The results revealed that 1. The components of academic administration towards excellence in private schools consist of 4 components: school curriculum development, learning process development, internal supervision, and internal quality assurance. 2. The current conditions, desired conditions, and necessary needs for academic administration towards excellence in private schools in Northeastern Thailand revealed that the current overall status is at the high level. The desired conditions are also at the highest level. The highest priority needs for developing academic administration towards excellence were found to be the learning process development, internal supervision, internal quality assurance, and school curriculum development. 3. Strategies for academic administration towards excellence in private schools in Northeastern There are 4 strategies as follows: a strategy for curriculum development, a strategy for learning process development, and a strategy for internal supervision. and strategy for internal quality assurance 4. The evaluation of the strategies overall shows that they are highly suitable, highly feasible, and highly beneficial.